Response of a finite beam on a tensionless Pasternak foundation under symmetric and asymmetric loading - Coskun, Irfan; Engin, Hasan; Oezmutlu, Aydin (TECHNO-PRESS, 2008)
The static response of a finite beam resting on a tensionless Pasternak foundation and subjected to a concentrated vertical load is assessed in this study. The concentrated vertical load may be applied at the center of the beam, or it may be offset from the center. The tensionless character of the foundation results in the creation of lift-off regions between the beam and the foundation. An analytical/ numerical solution is obtained from the governing equations of the contact and lift-off regions to determine the extent of the contact region. Although there is no nonlinear term in the equations, the problem shows a nonlinear character since the contact region is not known in advance. Due to that nonlinearity, the essentials of the problem (the coordinates of the lift-off points) are calculated numerically using the Newton-Raphson technique. The numerical results are presented in figures to illustrate the behaviours of the free-free and pinned-pinned beams under symmetric or asymmetric loading. The figures illustrate the effects of the shear foundation parameter and the symmetric and asymmetric loading options on the variation of the contact lengths and the displacement of the beam.
Keywords: pasternak foundation; finite beam; lift-off; REISSNER-MINDLIN PLATES; ELASTIC-FOUNDATION; NONLINEAR VIBRATIONS; FORCED VIBRATIONS; SOIL; SEPARATION; BEHAVIOR; ONSET; Engineering